2019
DOI: 10.1111/cid.12770
|View full text |Cite
|
Sign up to set email alerts
|

Immediate occlusal vs nonocclusal loading of implants: A randomized prospective clinical pilot study and patient centered outcome after 36 months

Abstract: Background Immediate provisionalization reduces chair time and improves patient comfort. Purpose To analyze immediate functional loading vs nonfunctional loading with restorations in the posterior mandible for marginal bone defects, implant success/survival, and patient satisfaction. Materials and Methods A randomized controlled clinical trial was designed to assess these parameters based on 20 adult patients who underwent implant surgery, followed by immediate delivery of screw‐retained or cemented single or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…30 A recent clinical trial similarly found a survival rate of 98.2% at the implant level for implants that were immediately loaded. 31 When comparing these previous results with those present study, the survival rate was lower in the SI group, while that in the TI group was similar. This might have been due to differences in the design of the TI and SI fixtures, and closely related to the primary stability achieved.…”
Section: Insertion Torque and Isqsupporting
confidence: 81%
“…30 A recent clinical trial similarly found a survival rate of 98.2% at the implant level for implants that were immediately loaded. 31 When comparing these previous results with those present study, the survival rate was lower in the SI group, while that in the TI group was similar. This might have been due to differences in the design of the TI and SI fixtures, and closely related to the primary stability achieved.…”
Section: Insertion Torque and Isqsupporting
confidence: 81%
“…Inter‐rater agreement (kappa score) was 0.63 for the title/abstract and 0.96 for the full‐text screens. A total of 153 studies were categorized as potentially relevant, eight of which could be included upon contacting their authors (Daher et al, 2019 ; Göthberg et al, 2018 ; Oxby et al, 2015 ; Payer et al, 2010 ; Si et al, 2016 ; Siebers et al, 2010 ; Simons et al, 2015 ; Vogl et al, 2019 ). Fourteen studies were finally included: Six RCTs, five cohort (four observational cohort and one case–control) studies, and three case series (two prospective and one retrospective).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding RCT studies, 3 of them (Daher et al, 2019 ; Fung et al, 2011 ; Van Nimwegen et al, 2015 ) were evaluated as having some concerns in terms of risk bias. Two were rated with high risk of bias (Romanos et al, 2016 ; Vogl et al, 2019 ), and only one was rated with low risk of bias (Göthberg et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher primary stability, nonocclusally loaded temporary restorations during a 3-month healing, splinted implants, and biocompatible prosthetic materials may reduce the risk of implant failure. 25 26 27 28 For partial prostheses, implants were splinted to support a preferable force distribution to the bone-implant interface under functional occlusion. The lateral forces were reduced by restricting working side contacts to the canines to retain implant micromotions.…”
Section: Discussionmentioning
confidence: 99%